2016
DOI: 10.1155/2016/3758590
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Changes following Acute Ethanol Intoxication in Healthy Men: A Crossover Study

Abstract: Alcohol is a known modulator of the innate immune system. Owing to the absence of human studies, alcohol's effect on circulating cytokine profile remains unclear. We investigated the effect of acute high dose alcohol consumption on systemic cytokine release. After an overnight fasting, alcohol-experienced healthy male volunteers (N = 20) aged 25–45 years were given oral ethanol in the form of vodka (4.28 mL/kg) which they drank over a period of 30 minutes reaching peak blood alcohol concentration of 0.12% (SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…When the effect of acute high‐dose alcohol consumption on blood levels of cytokines was evaluated in alcohol‐experienced healthy male adult volunteers (vodka, 4.28 ml/kg), serum levels of IL‐1Ra were found to be elevated and the levels of the chemokine MCP‐1 decreased acutely followed by a sustained elevation levels of MCP‐1, even blood alcohol level had returned to nondetectable levels (Neupane et al, ). Taken together, these findings indicate that, in the adult, multiple cycles of alcohol exposure (Marshall et al, ; Zhao et al, ) and/or prior EtOH exposure can produce long‐lasting increases in the expression of neuroimmune genes, microglial activation, and elevated levels of serum cytokines (Crews and Vetreno, ; Zou and Crews, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the effect of acute high‐dose alcohol consumption on blood levels of cytokines was evaluated in alcohol‐experienced healthy male adult volunteers (vodka, 4.28 ml/kg), serum levels of IL‐1Ra were found to be elevated and the levels of the chemokine MCP‐1 decreased acutely followed by a sustained elevation levels of MCP‐1, even blood alcohol level had returned to nondetectable levels (Neupane et al, ). Taken together, these findings indicate that, in the adult, multiple cycles of alcohol exposure (Marshall et al, ; Zhao et al, ) and/or prior EtOH exposure can produce long‐lasting increases in the expression of neuroimmune genes, microglial activation, and elevated levels of serum cytokines (Crews and Vetreno, ; Zou and Crews, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical and experimental data suggest that alcohol may be an immunomodulatory agent (Afshar et al, ; Szabo and Mandrekar, ). Alcohol exposure can impact systemic and brain innate immune signaling leading to activation of pro‐inflammatory cytokine pathways (Szabo and Saha, ), variation in serum cytokine levels (Gonzalez‐Quintela et al, ; Neupane et al, ), and induction of neuroinflammation (Crews et al, ; Crews et al, ; de Timary et al, ; Qin et al, ).…”
mentioning
confidence: 99%
“…The immune system is one candidate mediator of the alcohol hangover. Studies have shown inflammatory effects after acute alcohol administration, such as significantly elevated serum cytokine levels 2 h after drinking [ 7 ]. It has been hypothesized that these inflammatory effects persist over longer time, and/or have an influence on the presence or severity of a next-day alcohol hangover [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a blood alcohol concentration (BAC) of 0.08% (17.4 mM) is the legal limit for driving in the United States and many other countries, much higher BACs can be reached following acute heavy alcohol consumption [49, 50]. As such, a BAC of 0.4% (87 mM) is typically lethal in humans.…”
Section: Discussionmentioning
confidence: 99%